2020
DOI: 10.1016/j.worlddev.2020.105104
|View full text |Cite
|
Sign up to set email alerts
|

Equity as both a means and an end: Lessons for resilient food systems from COVID-19

Abstract: Highlights COVID-19 has exposed interconnected weaknesses of food, social and economic systems. Levels of food insecurity have increased by 83-132 million people mainly due to food access disruptions and exacerbated poverty. Those who are food insecure are more likely to suffer from health conditions that cause more severe symptoms of COVID-19. Food workers are essential but are treated as sacrificial, with racialized migrant food worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
105
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 16 publications
1
105
0
Order By: Relevance
“…Current reporting of COVID-19 in India focuses on the demographics of age and state, with almost no publicly available COVID-19 data disaggregated by social determinants such as disability, religion, caste and rurality (personal communication with others researching disparities in India). This study joins the call by others for research and data that uses an intersectional lens and disaggregated data in order to address the social inequities at the intersection of poverty, disability, caste and religious discrimination and gender [ 7 , 12 , 23 , 45 , 46 ] and further calls for increased attention to the assets and resources employed by individuals [ 43 ] and communities to cope and be resilient in adversity such as the COVID-19 crisis [ 47 ].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Current reporting of COVID-19 in India focuses on the demographics of age and state, with almost no publicly available COVID-19 data disaggregated by social determinants such as disability, religion, caste and rurality (personal communication with others researching disparities in India). This study joins the call by others for research and data that uses an intersectional lens and disaggregated data in order to address the social inequities at the intersection of poverty, disability, caste and religious discrimination and gender [ 7 , 12 , 23 , 45 , 46 ] and further calls for increased attention to the assets and resources employed by individuals [ 43 ] and communities to cope and be resilient in adversity such as the COVID-19 crisis [ 47 ].…”
Section: Discussionmentioning
confidence: 77%
“…Compounding disadvantage related to intersectional identity such as low literacy, female gender, disability, landlessness, dwelling in poor urban housing areas and widowhood led to increased and significant mental distress for most participants. Our findings suggest people already disadvantaged by their social identity and structural exclusions are more likely to experience further social exclusion, greater health needs, reduced access to care and ultimately, worse outcomes in the COVID-19 crisis [ 7 , 32 , 44 ], which has acted as an inequality amplifier [ 16 , 27 , 45 ]. Women in our study particularly reported bewilderment and low knowledge about COVID-19, and other intersectional studies of disasters have shown that women are more likely than men to be disadvantaged due to their reduced access to the protective attributes such as literacy, education, paid employment and political decision-making which are critical resilience factors in disaster [ 4 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result was that, in addition to changing food purchase patterns, the pandemic also generated an increase in the losses of these products in retail markets with a consequent reduction in traders' income [8]. An extraordinary situation has arisen in which the interconnected deficiencies of food, social and economic systems were exacerbated [8,9]. As a result of the pandemic, problems that threatened food security arose in Brazil, such as reduced cultivation and production of food, supply, and access to the centers of consumption for distribution.…”
Section: Introductionmentioning
confidence: 99%
“…In a "just" society, access to healthy food should be treated as a universal human right 6 , not as something that depends on purchasing power as any non-essential good (Klassen and Murphy, 2020). In a market-based economy the eradication of poverty (SDG #1) goes hand in hand with the eradication of hunger (SDG #2).…”
Section: Policy Priorities Highlighted By the Covidmentioning
confidence: 99%